Effect of community-based health insurance on the use of health service and perceived quality of care in Bacho Woreda, central Ethiopia: A mixed method study - Chala Damena Heyi; Anagaw Derseh; Berhan Tassew (Clinical Epidemiology and Global Health, 2025)
Background: Ethiopia has made a significant contribution towards Community Based Health Insurance (CBHI). However, evidence on the effect, use, and perceived quality of CBHI in the study area was scanty. Hence, this study aimed to assess the effects of a community-based health insurance scheme on the utilization of outpatient care, to assess factors affecting enrollment in the CBHI scheme, and explore the perception of the enrollee on the quality of care they received in Bacho Woreda, South West Shoa, Ethiopia. Methods: A facility-based Mixed method was conducted in Bacho District, central Ethiopia from December 2021 to May 30/2022. Quantitative data was collected using a structured questionnaire among a randomly selected sample of 386 (126 member and 240 non-members) household heads. While, qualitative information was gathered using focus group discussions among purposively selected CBHI members to complement the findings from the household survey. A logistic regression model was used to assess factors affecting enrollment in the CBHI scheme and to assess the effect of CBHI on outpatient service utilization. A bi-variable analysis of explanatory variables, including CBH scheme membership status, with the outcome variable of the study was computed. Then, all the independent variables that were significant in the bi variable analysis were taken for multiple logistic analysis. The qualitative data was summarized and presented concurrently alongside the quantitative data by using the thematic analysis technique. Result: A total of 386 respondents with a response rate of 95.3 %. The majority 219(56.7 %) of the study participants's’ age range from 18 to 35 years with a mean of 36.096 + 13.51796(33). Around half 191(49.5 %) of the study participants were farmers. The result revealed that there is a significant association between CBI participation and outpatient service utilization (AOR; 4.207, 95 % CI; 2.112, 8.380). In addition to this marital status of never married is significantly associated with OPD service utilization (AOR; 0.097, 95 % CI; 0.010, 0.970). The satisfaction of respondent with the service they received during their visit was also assessed and 60 (47.6 %) and 48(38.1 %) was very satisfied with the overall quality of service and availability of drug/medical supplies, respectively. 49(38.9 %) and 50(39.7 %) of respondents were satisfied with the availability of diagnostics and the cleanliness of the facility. Conclusion: The Members of CBHI were highly utilized in their health care and more likely to attend health care providers even for simple sickness. The perception of the respondents regarding improvement in service quality after the facility had been contracted by the CBHI scheme there was improvement in overall quality of service. Regarding to factor affects the incidence of participation in CBHI scheme has been assessed and it reveal that age between 36 and 50 years were 72.4 % less likely to participate in CBHI scheme compared to those who are between 51 and 86 years.